ANALISIS EFEKTIFITAS MARKETING DIGITAL DAN LAPORAN KEUANGAN DALAM PENINGKATAN PRODUKSI GULA MERAH SIWALAN DI KABUPATEN SUMENEP - Pranata, Mohammad Firlie; Rohmaniyah, Rohmaniyah (Universitas Madura, 2025)
Indonesia is entering the era of digitalization, people are starting to trade digitally. The online market is increasingly becoming a great hope for fast profits, switching from conventional stores to online stores is becoming commonplace. This is a challenge for business people to find human resources who are able to operate computers or can carry out online sales or what is called digital marketing. Digital marketing is expected to be able to promote existing products in a business in the digital world with the ability to dominate the digital market. Sumenep is a city that is geographically located at the eastern tip of Madura Island. Sumenep is also a city that produces Siwalan brown sugar. Siwalan brown sugar is an important part of life in Sumenep as a food sweetener and is also long-lasting for storage. In 2023, siwalan brown sugar businesses will begin to become extinct and will almost become extinct due to production materials and human resources becoming less interested in this business. So the researcher will conduct research on digital marketing in increasing siwalan brown sugar production in Sumenep district. The method used in qualitative research is by conducting interviews and observations and processing data to obtain solutions and methods that are suitable for solving these problems, the results of the research With the existence of digital marketing, Siwalan brown sugar business actors need special training and support from the village and government in becoming a sales platform so that the community can sell Siwalan brown sugar more quickly and produce it on a large scale every day. Regarding production material issues, there is a need for growers. new siwalan tree so that it can be passed on to the next generation, and the importance of financial reports in recording is very important to increase consumer confidence and ease of managing finances.